Virtual reality and smartphone utilisation for the examination and enhancement of working memory load for visual and auditory dual tasking. - Theunissen, Tjeu P. M.; Pieterse, Marcel E.; De Cort, Klara; Matthijssen, Suzy J. M. A.; Schruers, Koen R. J. (Memory, 2025)
During Eye Movement Desensitisation and Reprocessing (EMDR) therapy, patients recall traumatic memories while performing dual attention tasks to tax the limited capacity of the working memory (WM). Increasing WM load during recall has shown to improve memory-degrading effects. This research aims to explore how technological tools can be used to more effectively increase WM load. Two experiments involving healthy participants utilised Random Interval Repetition (RIR) tasks to investigate the WM-taxing effects of specific digital dual-attention tasks and task manipulations. In experiment 1 (N = 41), conducted in a lab-based virtual reality setting, participants performed auditory RIR tasks while varying the speed and direction of eye movements (EM), with or without an additional visual RIR task. Experiment 2 (N = 49), conducted online via a smartphone application, compared solo and combined auditory and visual RIR tasks presented either simultaneously or serially under varying EM speeds. Results showed that combining RIR tasks increased auditory RTs, while a simultaneous combination and higher EM speeds selectively increased visual RTs only. These findings suggest that task addition and manipulation effectively increase WM load, though the involvement of WM sub-modalities and high-demand tasks influences their effects. These insights could refine face-to-face and online EMDR practices and optimise therapeutic effectiveness.